2006
DOI: 10.1186/1471-2296-7-65
|View full text |Cite
|
Sign up to set email alerts
|

Implementing referral guidelines: lessons from a negative outcome cluster randomised factorial trial in general practice

Abstract: Background: Few patients with lower bowel symptoms who consult their general practitioner need a specialist opinion. However data from referred patients suggest that those who are referred would benefit from detailed assessment before referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 17 publications
2
47
0
Order By: Relevance
“…In contrast, the high-quality RCTs failed to show an improvement in aspects of management and knowledge using education, 18,19 diagnostic accuracy using audit and feedback, 28 and referral accuracy and investigation using decision-support software. 23,26 Mixed effects were found in aspects of management using educational material and a guideline. 32 It was not always possible to pinpoint which particular aspects of the interventions led to particular improvements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, the high-quality RCTs failed to show an improvement in aspects of management and knowledge using education, 18,19 diagnostic accuracy using audit and feedback, 28 and referral accuracy and investigation using decision-support software. 23,26 Mixed effects were found in aspects of management using educational material and a guideline. 32 It was not always possible to pinpoint which particular aspects of the interventions led to particular improvements.…”
Section: Discussionmentioning
confidence: 99%
“…20,22,25,32 Therefore, it cannot be determined whether any of the reported improvements persisted. Less than half of the 22 studies included recruited more than 100 participants, 11,15,17,21,23,24,26,29,30,32 and several studies suffered from a high dropout rate, 18,19,28,32,33 with only 18% of participants in 6 months. How intervention was assessed: a baseline clinical self-audit of skin excisions was carried out over 6 months, followed by a feedback report and provision of the educational module over the next 6 months.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous UK trial similarly found limited clinical value in a referral proforma. 12 An earlier systematic review failed to identify any robust studies that demonstrate an impact from the quality of referral letters on patient outcomes. 7 The data reported here suggest that semi-structured, guideline informed referral letters are unlikely to influence the scheduling of appointments by specialists.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%